Detection of Staphyl ococcus aureus capsules producer isolated from bovine and buffaloes mastitis - G. N. Shamoon (Iraqi Journal of Veterinary Sciences, 2006)
This study was done for the detection of capsulated Staphylococcus aureus strains which were isolated from bovine & buffaloes Mastitis. 23 (57.5 %) & 8 (53 %) strains of these bacteria were isolated, 6 (26 %) & 2 (13.3 %) were capsule producing strains, and that 9 (39.1 %) & 4 (26.6 %) were slime producing strains, respectively. An increase in the number of capsules and slim producing strains was observed following growing of these bacteria in culture media containing glucose and milk. The experimentally performed histo-pathological study, revealed presence of capsules in lung sections stained with Hematoxylin–Eosin as a halo areas appeared around the bacterial cells. In addition to a strong positive reaction with periodic acid shiffs.